2022
DOI: 10.56093/ijans.v92i1.120931
|View full text |Cite
|
Sign up to set email alerts
|

Effect of mother contact and voluntary colostrum suckling on growth, health and stress of neonatal buffalo calves

Abstract: The aim of present study was to investigate the effect of full mother contact and voluntary colostrum suckling on the health, stress and growth performance of neonatal Murrah buffalo calves. For this, two experiments (exp.) were conducted involving exp.1, 24 mother-calf pairs were divided into three equal groups (eight pairs/each group). In no mother contact (NC) group, weaning was allowed immediately after birth. In restricted mother contact (RC) group, restricted contact was allowed twice daily. In fence-lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…The findings of the current study complements previous research suggesting that buffalo calves are born agammaglobulaemic and rely heavily on maternal colostrum for passive immunity (Bharti et al ., 2015; Hedegaard and Heegaard, 2016). They need an adequate amount of colostrum at frequent intervals to promote the development of appropriate levels of passive immunity (Hammon and Blum, 1998; Choudhary et al ., 2022). Thus, this illustrates the real importance of provision of full physical calf–dam contact and consequent full opportunity for ingestion of colostrum compared to a limited contact and artificial feeding system for buffalo calves.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The findings of the current study complements previous research suggesting that buffalo calves are born agammaglobulaemic and rely heavily on maternal colostrum for passive immunity (Bharti et al ., 2015; Hedegaard and Heegaard, 2016). They need an adequate amount of colostrum at frequent intervals to promote the development of appropriate levels of passive immunity (Hammon and Blum, 1998; Choudhary et al ., 2022). Thus, this illustrates the real importance of provision of full physical calf–dam contact and consequent full opportunity for ingestion of colostrum compared to a limited contact and artificial feeding system for buffalo calves.…”
Section: Discussionmentioning
confidence: 99%
“…With respect to the adverse consequences of separation in cattle and buffaloes, recent studies have shown that a fenceline mother-calf system (FCMC) can reduce stress and improve the health and growth of dairy and buffalo calves (Johnsen et al, 2016;Hassan et al, 2019;Choudhary et al, 2022). Sirovnik et al (2020) defined FCMC as limited physical contact between a mother and her own calf, allowing olfactory, visual, auditory and limited tactile contact.…”
mentioning
confidence: 99%
See 2 more Smart Citations